Adoção de práticas de acessibilidade web no desenvolvimento e implantação de governo eletrônico no Brasil - Balisa, Marcelo Adalton (2018)
The use of Electronic Government as a State policy can contribute to making the public sector more efficient, making complex and bureaucratic activities simpler. However, Electronic Government Web systems, when not properly designed, make it difficult for people with disabilities to have access to these policies. Although there is specific legislation that obliges government agencies to make their Web systems accessible, it is still possible to find many Electronic Government Web systems that have accessibility problems. In the specialized literature there are not many reports on the adoption of Web accessibility practices in public agencies in the development and implementation of Electronic Government services, nor studies that explain the factors that contribute to or hinder the adoption of accessibility practices. In this work, the objective was to investigate how managers and developers of Information Technology of Brazilian federal agencies have adopted innovations related to accessibility practices in the development, acquisition or implementation of Electronic Government systems. For that, an elaborated questionnaire was applied to several Brazilian governmental organs. The questionnaire was based on the Theory of Diffusion of Innovations, specifically the Adoption of Innovations model. The perceived attributes of innovation, such as relative advantage, compatibility, complexity, experimentability, and observability, made up the constructs that determined the adoption of innovation. The other variables of the Adoption of Innovations model, namely, decision type, communication channels, nature of the social system and degree of commitment of the agent of changes, also composed the constructs of the research model. The innovation in this study is the Web accessibility practices. The research obtained 203 valid answers. The results showed that the nature of the social system is the most influential variable in the adoption of eMAG accessibility guidelines. The constructs relative advantage, complexity and degree of commitment of the change agent also presented some evidence of influence in the adoption of the studied innovation. Other important aspects have been identified as the fact tha t most participants recognize the legal obligation to implement accessible eGovernment Web systems, but do not believe that they can be punished for not complying with the legislation.